Israel Continues to Expand Its Settlements - V. Sukhanov (Международная аналитика)
The article analyzes the influence of the religious aspects on the political processes in Israel. Special attention is paid to the role of religion in the Palestinian-Israeli conflict. The author shows the trend towards politicization of religion and characterizes the process as unconstructive, which prevents to a peaceful settlement of the Palestinian-Israeli conflict.The article also discusses the interaction between secular and religious principles in the State of Israel, estimates the current situation, highlights the importance of the religious component in the political life of Israel.